2011
DOI: 10.1186/1476-9255-8-4
|View full text |Cite
|
Sign up to set email alerts
|

Low level bacterial endotoxin activates two distinct signaling pathways in human peripheral blood mononuclear cells

Abstract: BackgroundBacterial endotoxin, long recognized as a potent pro-inflammatory mediator in acute infectious processes, has more recently been identified as a risk factor for atherosclerosis and other cardiovascular diseases. When endotoxin enters the bloodstream, one of the first cells activated is the circulating monocyte, which exhibits a wide range of pro-inflammatory responses.MethodsWe studied the effect of low doses of E. coli LPS on IL-8 release and superoxide formation by freshly isolated human peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Furthermore, the expression of defensins and proinflammatory cytokines has been reported to be dependent on breed or cell, affected by the dose of LPS, and depended on the time of stimulation (Ebers et al 2009, Blomkalns et al 2011, Sorensen et al 2011). Therefore, we developed an in vitro model to investigate the timing of response to LPS on patterns of gene expression in rooster SCs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the expression of defensins and proinflammatory cytokines has been reported to be dependent on breed or cell, affected by the dose of LPS, and depended on the time of stimulation (Ebers et al 2009, Blomkalns et al 2011, Sorensen et al 2011). Therefore, we developed an in vitro model to investigate the timing of response to LPS on patterns of gene expression in rooster SCs.…”
Section: Discussionmentioning
confidence: 99%
“…This has been illustrated in human endothelial cells treated with dihydrotestosterone for 4 hours [56] and murine macrophages exposed to testosterone for 12-24 hours [57]. However, a recent study has shown that ROS generation is independent of TLR4 activation in monocytes [35]. Another explanation could be that bacteria and zymosan particles are recognized through several pathways, such as TLR2, dectin-1, and complement receptor 3 [58][59][60], which may lead to compensation for inhibitory effects, compared to LPS recognition [61].…”
Section: Discussionmentioning
confidence: 87%
“…In innate immunity, IL-8 is reported to be produced mainly by monocytes [35][36][37][38], whereas granulocytes only secrete a limited amount of the cytokine [45][46][47]. It is therefore interesting that differentiated HL-60 cells secrete a considerable amount of IL-8 ( Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations